Brain Network and Synaptic Plasticity Changes Associated with Electroconvulsive Therapy for Depression: A Multilevel Review - Yihan Jiang; Xinying Jiang; Yuting Huang; Xiaohui Yu (International Journal of Public Health and Medical Research, 2026)
Electroconvulsive therapy (ECT) is an important treatment for severe, treatment-resistant, or high-risk depression, yet the relationship between its antidepressant effects, brain network changes, and cellular and molecular processes remains incompletely understood. Recent advances in multimodal magnetic resonance imaging (MRI), magnetic resonance spectroscopy (MRS), molecular biology, and animal electroconvulsive stimulation models have provided multilevel evidence for understanding the neurobiological mechanisms of ECT in depression. Current studies suggest that ECT is accompanied by changes in functional connectivity within large-scale brain networks, including the default mode network (DMN), the frontoparietal control network (FPCN), and prefrontal-limbic circuits. In parallel, processes involving neurotransmission, brain metabolism, neurotrophic factors, inflammatory responses, and synaptic plasticity may provide biological clues for interpreting these network-level changes. This review summarizes evidence related to brain network reorganization and synaptic plasticity-associated regulation in ECT for depression, and discusses how findings across levels may be integrated to inform future mechanistic research and treatment-response prediction.